Effect of rice husk morphology on the ability to synthesize silicon carbide by pyrolysis method - Kien, Kieu Do Trung; Ong Dieu, Hanh; Nguyen Hoang Thien, Khoi; Huynh Ngoc, Minh (Vietnam Journal of Science and Technology, 2024)
Silicon carbide (SiC) is a mineral with good technical properties and high economic value. However, the synthesis of SiC is expensive because it is synthesized at a high-temperature environment (above 1500oC). The synthesis of SiC from biomass can significantly reduce the synthesis temperature. One commonly used biomass material for synthesizing SiC is rice husk. However, the ability to synthesize SiC depends on the shape of the rice husk. The influence of the morphology of rice husk on the ability to synthesize SiC was studied in this study. Experimental results showed that the original rice husk would give better SiC formation capacity than the rice husk powder. The amount of SiC formed using the original rice husk when impregnated by sodium silicate solution and pyrolysis at 1200oC is 18.3% (wt%.). With rice husk powder, it is 15.12% (wt%.). The results of analysis of the mineral composition, functional groups, and morphologies by X-ray diffraction (XRD), Fourier Infrared Transform Method (FT-IR), and Scanning Electron Microscopy (SEM) found that the polymorphy of SiC is α-SiC and β-SiC. These minerals are the basis for SiC from rice husks, which can be applied as wear-resistant materials.